Recent introductions reveal differential susceptibility to parasitism across an evolutionary mosaic - Tepolt, Carolyn K.; Darling, John A.; Blakeslee, April; Fowler, Amy E.; Torchin, Mark E.; Miller, A. Whitman; Ruiz, Gregory M. (My University, 2019)
Parasitism can represent a potent agent of selection, and introduced parasites have the potential to substantially alter their new hosts' ecology and evolution. While sig‐ nificant impacts have been reported for parasites that switch to new host species, the effects of macroparasite introduction into naïve populations of host species with which they have evolved remain poorly understood. Here, we investigate how the estuarine white‐fingered mud crab (Rhithropanopeus harrisii) has adapted to parasit‐ ism by an introduced rhizocephalan parasite (Loxothylacus panopaei) that castrates its host. While the host crab is native to much of the East and Gulf Coasts of North America, its parasite is native only to the southern end of this range. Fifty years ago, the parasite invaded the mid‐Atlantic, gradually expanding through previously naïve host populations. Thus, different populations of the same host species have expe‐ rienced different degrees of historical interaction (and thus potential evolutionary response time) with the parasite: long term, short term, and naïve. In nine estuaries across this range, we examined whether and how parasite prevalence and host sus‐ ceptibility to parasitism differs depending on the length of the host's history with the parasite. In field surveys, we found that the parasite was significantly more preva‐ lent in its introduced range (i.e., short‐term interaction) than in its native range (long‐ term interaction), a result that was also supported by a meta‐analysis of prevalence data covering the 50 years since its introduction. In controlled laboratory experi‐ ments, host susceptibility to parasitism was significantly higher in naïve hosts than in hosts from the parasite's native range, suggesting that host resistance to parasitism is under selection. These results suggest that differences in host–parasite historical interaction can alter the consequences of parasite introductions in host populations. As anthropogenically driven range shifts continue, disruptions of host–parasite evo‐ lutionary relationships may become an increasingly important driver of ecological and evolutionary change.
Keywords: adaptation in invasion, biological introductions, host–parasite evolution, Loxothylacus panopaei, mud crabs, parasite biogeography, Rhithropanopeus harrisii, rhizocephalans